2023
DOI: 10.1088/1755-1315/1168/1/012048
|View full text |Cite
|
Sign up to set email alerts
|

Environmental awareness and intention to reduce food waste among urban people

Abstract: Environmental issues and food waste are still crucial issues today. Indonesia, which is still facing problems of food security and stunting, is reported to be ranked second in the world as a contributor to food waste. This study aimed to measure the level of environmental awareness and intention to reduce food waste among urban people in Indonesia. One thousand ninety-eight samples were collected from five major provincial cities: Jakarta, Bandung, Semarang, Yogyakarta, and Surabaya. The results show that envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…[32] who pointed out that consequences awareness was significantly correlated with the intention to return medications appropriately. The same results were also obtained in several behaviors associated with reducing waste [7,29,63,67,72].…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…[32] who pointed out that consequences awareness was significantly correlated with the intention to return medications appropriately. The same results were also obtained in several behaviors associated with reducing waste [7,29,63,67,72].…”
Section: Discussionsupporting
confidence: 74%
“…[ 67 ] showed that e-waste toxicity knowledge affects the recycling e-waste behavior. In a recent study on food waste in Indonesia, Purwanto et al [ 72 ] find out that intention to minimize waste is significantly determined by environmental awareness.…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%